Sweet orange trees grafted on selected rootstocks fertilized with nitrogen, phosphorus and potassium - Quaggio, José Antônio; Junior, Dirceu Mattos; Cantarella, Heitor; Stuchi, Eduardo Sanches; Sempionato, Otávio Ricardo (Pesquisa Agropecuaria Brasileira, 2004)
The majority of citrus trees in Brazil are grafted on 'Rangpur lime' (Citrus limonia Osb.) rootstock. Despite its good horticultural performance, search for disease tolerant rootstock varieties to improve yield and longevity of citrus groves has increased. The objective of this work was to evaluate yield efficiency of sweet oranges on different rootstocks fertilized with N, P, and potassium. Tree growth was affected by rootstock varieties; trees on 'Swingle' citrumelo [Poncirus trifoliata (L.) Raf. × C. paradisi Macf.] presented the smallest canopy (13.3 m3 in the fifth year after tree planting) compared to those on 'Rangpur lime' and 'Cleopatra' mandarin [C. reshni (Hayata) hort. ex Tanaka] grown on the same grove. Although it was observed an overall positive relationship between canopy volume and fruit yield (R2 = 0.95**), yield efficiency (kg m-3) was affected by rootstocks, which demonstrated 'Rangpur lime' superiority in relation to Cleopatra. Growth of citrus trees younger than 5-yr-old might be improved by K fertilization rates greater than currently recommended in Brazil, in soils with low K and subjected to nutrient leaching losses.